2007
DOI: 10.1007/s10974-007-9119-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic electrical stimulation on long-term denervated muscles of the rabbit hind limb

Abstract: We investigated the extent to which activity induced by chronic electrical stimulation could restore the mass and contractile function of rabbit tibialis anterior (TA) muscles that had undergone atrophy as a result of prolonged denervation. Denervation was carried out by selectively interrupting the motor nerve branches to the ankle dorsiflexors in one hind limb. Stimulators were implanted, with electrodes on the superficial and deep surfaces of the denervated TA muscle. Ten weeks later, the mass and mid-belly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 23 publications
3
47
0
2
Order By: Relevance
“…Another study showed that intramuscular administration of a plasmid engineered to induce VEGF expression enhanced preserved grip strength in a rat model of amyotrophic lateral sclerosis which suggests that VEGF administration might be neuroprotective and a practical approach for treating motor disorders [16]. Although data on muscle force restoration after musculoskeletal injury for this type of model were not available at the time we conducted our study, recently published studies [2,4] confirm the restoration of muscle force we observed.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Another study showed that intramuscular administration of a plasmid engineered to induce VEGF expression enhanced preserved grip strength in a rat model of amyotrophic lateral sclerosis which suggests that VEGF administration might be neuroprotective and a practical approach for treating motor disorders [16]. Although data on muscle force restoration after musculoskeletal injury for this type of model were not available at the time we conducted our study, recently published studies [2,4] confirm the restoration of muscle force we observed.…”
Section: Discussionsupporting
confidence: 66%
“…We assumed a 25% difference would be clinically important. The expected effect size greater than 20% for calculation was estimated from data on the use of longterm electrical stimulation to improve muscle force and muscle atrophy [2]. The calculation revealed that 11 animals would be required per group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, these findings support the hypothesis that electrical stimulation-induced changes in intracellular [Ca 2+ ] may mimic the lost nerve influence and may play a key role in modifying denervated muscle gene expression. Hence, these observations provide a potential molecular explanation of the muscle recovery that occurs in response to the rehabilitation strategy of FES in mammals and humans [3,5,38], which was developed as a result of empirical clinical observations [37,38]. In SCI patients after months of twitch training [37], and thus of intracellular [Ca 2+ ] transients, the restored muscle morphology and tetanic contractility agree with improvements of the synthesis/degradation balance of sarcolemmal, ECC, cytoskeleton and myofibrillar proteins.…”
Section: Resultsmentioning
confidence: 72%
“…[167][168][169][170][171] However, evidence has yet to be presented as to whether, and to what degree, preservation of a larger muscle mass and better functional properties of denervated muscles would promote functional recovery after reinnervation.…”
Section: Post-operative Electrical Stimulation Of Paralyzed Vibrissalmentioning
confidence: 99%